(3eLeY GdCMHGHs - (3eMeO Hf GdMSf Hf YHO Gddg GdMSjfjs; (3CHh fYje CMeO Hf YHO Gddg Hf CMeO Hf GSMGb GdCUHgGfjs
(3ChdgG (B:s
(3CeG HYO aEfi deG hbaJ Ydi cJGH MdjI GdChdjGA hWHbI GdCUajGA ddEeGe GdYdGeI CHh fYje CMeO Hf YHO Gddg Hf CMeO Hf ESMGb GdCUHgGfi CMHHJ Cf CLeY cJGHkG jchf deMGSfgG MGhjkG s
(3BNQgG (B:s
(3adeG cGO Cf jNQL bGd jG eHGQc EdMbg aQOg Ydi adeG QLY bGd hbGd CMeO GdRjOi cfJ ai eSLO GdMfja eY SajGf s
(3HgG fXGe GdJYbjHIs
(3hgh WHbGJ GdUhajIs
(3HChdg agQS HeMJhjGJ GdcJGH cJH HYV GdcdeGJ HGdMeQI s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs